Adaptation and mislocalization fields for saccadic outward adaptation in humans - Fabian Schnier; Eckart Zimmermann; Markus Lappe (Journal of Eye Movement Research)
Adaptive shortening of a saccade influences the metrics of other saccades within a spatial window around the adapted target. Within this adaptation field visual stimuli presented before an adapted saccade are mislocalized in proportion to the change of the saccade metric. We investigated the saccadic adaptation field and associated localization changes for saccade lengthening, or outward adaptation. We measured the adaptation field for two different saccade adaptations (14 deg to 20 deg and 20 deg to 26 deg) by testing transfer to 34 different target positions. We measured localization judgements by asking subjects to localize a probe flashed before saccade onset. The amount of adaptation transfer differed for different target locations. It increased with increases of the horizontal component of the saccade and remained largely constant with deviation of the vertical component of the saccade. Mislocalization of probes inside the adaptation field was correlated with the amount of adaptation of saccades to the probe location. These findings are consistent with the assumption that oculomotor space and perceptual space are linked to each other.